The effects of cultivation type and maturity stage on arsenic species concentration and carrageenan content in Kappaphycus spp. from Semporna, Sabah - Subramaniam, Ghanthimathi; Surugau, Noumie; Aziz, Nor Azwady Abd; Shukri, Radhiah; Muhammad, Kharidah (Springer Dordrecht, 2023)
Three Kappaphycus species (Kappaphycus striatus, Kappaphycus alvarezii, and Kappaphycus malesianus) were cultivated using two cultivation methods (longline and off-bottom) at four maturity stages with an interval of 20 days. The study was performed to evaluate the effects of cultivation type and maturity stages (0, 20, 40, and 60 days) on the arsenic (As) species concentration and carrageenan content in the seaweeds. It was found that As species concentration in Kappaphycus spp. grown using longline cultivation technique followed the order arsenate [As(V)] > dimethylarsenic acid (DMA) > arsenite [As(III)] > monomethylarsenic acid (MMA), and in off-bottom was DMA > As(III) > MMA > As(V). The principal component analysis (PCA) models for longline and off-bottom cultivations exhibited dominance of carrageenan content over As species concentration at 40 days of growth period of Kappaphycus spp. Among the cultivation techniques, longline datasets were inclined heavily towards carrageenan content vector, which was negatively correlated to the As species concentration in the PCA. The Kappaphycus spp. grown until 40 days using longline cultivation provided a high carrageenan content with less influence of As species contamination. These findings can impact the seaweed industry, where the farmers can attain sustainable yield of carrageenan that have less risk of rejection by the food safety authorities for As species contamination.